TECHNOLOGICAL MODERNIZATION OF FOREST ROADS CONSTRUCTION IN RUSSIA - Smirnov, Mikhail; Andrianov, Yuri; Chernyakevich, Victor (Journal of Applied Engineering Science, 2018)
The paper considers the basic problems of construction of wood roads in Russia. Lack of suffi cient quantity of roads functioning year round leads to annual isolation of almost 15 million inhabitants of forest settlements in autumn and in spring, absence of rhythm in timber-hauling process, increase in forest products cost. Two organizational methods of forest roads construction, namely, fl ow-line conveyor and non-fl ow-line conveyor ones are compared. According to the advanced fl ow-line conveyor method a complex stream is organized uniting specialized streams equipped with road machines and mechanisms for performing separate works. When the amount of work is small it is recommended to apply a non-fl ow-line conveyor method, either cyclic or inby. The experience of constructing a road in a forest, which does not provide any headworks and is carried out by a dredge only, is considered. It allows to lower expenses for construction works. Owing to the absence of stone road-building materials in the majority of forest regions of Russia a new design of a two-layer road covering from reinforced concrete slabs and the technology of its construction have been developed. The comparison of the suggested technology of forest roads construction with existing domestic technologies and the Finnish one has shown its effi ciency both in terms of money, and from the viewpoint of reduction of the number of necessary machines and equipment. The technology suggested has passed industrial approbation on running logging enterprises.